Pengaruh Kepercayaan Diri terhadap Kreativitas Gerak dalam Pengembangan Tari pada Dance Challenge Wonderland Indonesia di TikTok: Studi pada Siswa Kelas VII SMPN 26 Jakarta - Nur Fitriah, Nur Fitriah; Dinny Devi Triana; Kartika Mutiara Sari (Jurnal Pendidikan Tari, 2025)
High self-confidence allows individuals to believe in their abilities and encourages creativity in developing their potential. This study aims to describe the relationship between self-confidence and the ability to develop dance in the Wonderland Indonesia dance challenge, determine the correlation between students' movement creativity and their ability to develop dance, and describe the strength of the relationship between self-confidence and students' movement creativity in dance development.This study employs a correlational quantitative approach using a non-experimental research method. The research subjects were eighth-grade students at SMPN 26 Jakarta. Data analysis techniques involved correlation tests to examine the relationships between variables. The results indicate that self-confidence significantly influences the ability to develop dance, with a t-value of 3.032 and a significance level of 0.004, contributing 60.4% to dance development. Similarly, students' movement creativity also affects dance development, with a t-value of 4.497 and a significance level of 0.000, contributing 55.7%. Simultaneously, self-confidence and movement creativity have a significant impact on dance development, with an F-value of 13.633 and a significance level of 0.000 (<0.05).The study concludes that both self-confidence and students' movement creativity influence the ability to develop dance, both partially and simultaneously, in the Wonderland Indonesia dance challenge.